A study comparing the effectiveness of ondansetron versus ondansetron combined with dexamethasone for preventing postoperative nausea and vomiting in laparoscopic surgeries - Rajan B. Pandya; Deepika Sathe; Ankita Joshi; Vishwas Sathe (MGM Journal of Medical Sciences)
Background: Postoperative nausea and vomiting (PONV) frequently occur as a side effect of general anesthesia, which can be intensified by the introduction of gas into the peritoneal cavity to create pneumoperitoneum during laparoscopic surgeries. Aims and Objectives: This study examines the comparative effectiveness of ondansetron as a standalone treatment versus its combination with dexamethasone in preventing PONV during laparoscopic surgeries. The research aims to assess the efficacy and duration of anti-nausea and anti-vomiting effects provided by ondansetron alone and in combination with dexamethasone. Materials and Methods: The Institutional Ethics Committee (IEC) approved the trial materials and methods following thorough deliberation. Before surgery, written informed consent was obtained from all patients. Sixty patients were recruited for the study and randomly allocated into groups, denoted as Group O and Group D, each consisting of 30 patients. Group O received intravenous administration of 4 mg of ondansetron, while Group D received a combination of 4 mg of ondansetron and 4 mg of dexamethasone intravenously 30 min before extubation. Duration of Study: The research was conducted at MGM Medical College and Hospital, located in Navi Mumbai, Maharashtra, India, from May 2016 to May 2017. Results: In this study, mild and moderate nausea were more prevalent in Group O at the 4-h mark, but there was no notable difference at 24 h. Mild and moderate retching showed no significant variance at 4 h, but Group O exhibited significantly more at 24 h. Mild, moderate, and severe vomiting were inconsequential in both groups at 4 h, but Group O showed a higher incidence of mild and moderate vomiting at 24 h. Instances of severe vomiting were absent in both groups. The need for rescue antiemetics after 24 h and medication-related side effects did not show significant differences between the two groups. Conclusion: The incidence of PONV was reduced in the combination group (ondansetron + dexamethasone) compared to ondansetron alone. Consequently, the combination group had a lower requirement for rescue antiemetics. Thus, the effectiveness of combination therapy surpassed that of ondansetron alone.